The Benefit of Milk Consumption on Athletes - Yudha, Saddam Dwi Wira; Pamungkas, Agung Yera Setyo; Purnamawati, Az Zahra Asri; Andriansyah, Muhamad; Rustiadi, Tri (Universitas Negeri Semarang, 2022)
Milk provides nutrition for athletes both during training and during competition. Currently, many athletes are aware that drinking milk can improve athlete performance. Athletes must have knowledge of good nutrition. So that it can be applied in the lives of athletes. The purpose of this study was to find out what benefits can be obtained if athletes consume milk both during competition and training. The research methodology uses secondary data for the last 10 years from various library sources such as Google Scholar. The results of this study are milk can improve the performance of athletes both during matches and training. By consuming milk, the body's health can improve and the body's condition is more prime.